Assessment Practices of Practicum Supervisors - Samina Naseem, Anam Iqbal, Shafia Azam (JCTE, 2023)
Assessment, undoubtedly, plays a significant role, not only in helping students learn but also in improving instruction. Using assessment practices mentioned in the National Professional Standards for Teachers in Pakistan (2009) as an analytical framework, this qualitative study documented the assessment practices of practicum supervisors from three major teacher preparation programs (TPPs) in Rawalpindi and Islamabad. Faculty members who had served practicum twice and student teachers from the VIII semester were the participants. The main data sources - interviews and focused group discussion, were transcribed verbatim and coded using provisional themes. The analysis revealed that practicum supervisors from the three TPPs were not following NPSTP as a guide to assess student teachers’ (STs) teaching. This study underscores the role of practicum supervisors in improving learning experiences for STs during practicum and identifies the current assessment practices to suggest focusing on all the aspects i.e., lesson planning, management, assessment, and teaching, and should use the NPSTP’s assessment rubric for STs assessment to make practicum more beneficial and productive.